Different Setting Conditions Affect Surface Characteristics and Microhardness of Calcium Silicate-Based Sealers. (16th January 2018) - Yang, Dong-Kyu; Kim, Sunil; Park, Jeong-Won; Kim, Euiseong; Shin, Su-Jung
Abstract : Objective . To investigate the effect of different setting conditions on surface microhardness and setting properties of calcium silicate-based sealers. Methods . Three sealers, EndoSequence Bioceramic (BC; Brasseler USA, Savannah, GA, USA), Endoseal MTA (ES; Maruchi, Wonju, Korea), and Well-Root ST (WR; Vericom, Chuncheon, Korea), were compared. Specimens were exposed to either butyric acid (pH 5.4) or phosphate-buffered saline (PBS [pH 7.4]) for 48 h and stored at 100% humidity for 12 days. The control specimens were stored at 100% humidity for 14 days. Surface microhardness was measured, topographic changes were observed, and phase analysis was performed using X-ray diffraction. Microhardness according to storage conditions was compared using one-way analysis of variance and Tukey's multiple comparison tests (P < . 05 ). Results . The BC and ES sealers exhibited decreased microhardness when stored in acid or PBS compared with control (P < . 05 ). In the WR group, acid exposure lowered microhardness of the specimens compared with control (P < . 05 ). Scanning electron microscopy revealed different topographies in specimens from all tested sealers exposed to acid or PBS. Conclusion . The surface microhardness of calcium silicate-based sealers was reduced by exposure to either acid or PBS. Acid solutions, however, had a more detrimental effect than PBS.